Identification, abundance, and behavior of North American bobcat (Lynx rufus) along road mitigation structures designed for endangered species in South Texas - Hanley, Victoria; Ryer, Kevin; Rahman, Md Saydur; Young, John H.; Kline, Richard J. (Frontiers in Ecology and Evolution, 2025)
Endangered species are increasingly used as the target species in implementing and constructing new wildlife crossing structures (WCS). Highways in South Texas fragment the landscape and result in high road mortality for endangered species such as ocelots (Leopardus pardalis, a medium-sized spotted wild cat). In response, the Texas Department of Transportation constructed nine WCS on Farm-to-Market 106 (FM 106), a road which bisects Laguna Atascosa National Wildlife Refuge in Cameron County, Texas. With ocelots being rare and elusive, bobcats (Lynx rufus) are often used as a surrogate species to study felid behavior at road mitigation structures in South Texas. Bobcats have unique markings which allow them to be individually identified. Three methods of individual identification of bobcats using camera trap photos were compared: visual identification, HotSpotter, and a spatio-temporal strategy, with manual visual identification being the most effective. Using this method, 78 bobcats were identified across the 23 sites along FM 106 including: 17 residents, 52 transients, and 9 juveniles. Their interactions at road mitigation structures were further analyzed to determine the effectiveness of facilitating bobcat movement safely beneath the road. The number of bobcat individuals at a WCS per month was a significant predictor of the number of bobcat interactions (p < 0.001). Canopy cover was a significant predictor of bobcat crossings, with more crossings occurring in dense canopy cover than in mixed or open areas (p < 0.001). For marking behaviors at WCS, bobcat sex was not a significant factor (p = 0.749). However, residency status significantly affected marking behavior, with resident bobcats marking more frequently than transients (p < 0.001). The number of days between interactions at WCS decreased as the number of interactions since initial contact with a WCS increased, indicating that bobcats interacted more frequently with WCS over time. However, the rate of successful crossings did not increase. One male ocelot was observed at two WCS with dense vegetation, these were also the two crossings with the greatest frequency of bobcat activity and marking behaviors.